Online service failure: diagnosing customer’s evaluation of critical incidents outcomes - Maisarah Ahmad; Suhaila Abdul Kadir; Syed Shah Alam; Nur Sa'adah Muhamad; Nor Suryani Ab. Ghani; Noorasikin Mohd Mandak (2015)
The rapid propagation of the internet over the last decades has changed the way customers and service providers conducting business. This study focuses on customer’s evaluation on service encounters within an online setting and its consequences. Critical incident technique (CIT) was conducted to gain understanding of customer’s perception on ‘satisfactory’ and ‘dissatisfactory’ online service encounter and to explore the underlying antecedents of customer’s evaluation following an online service failure. A total of 26 written accounts of these critical incidents were content analysed through data obtained from interviews and open ended questionnaires sampled from online service customers. Four categories of failure have been classified: (a) unavailable service, (b) slow service, (c) systems failure and (d) other core service failure, adding another dimension to Bitner et al.’s (1990) 3-category responses to service failure. In particular, responses to technical systems failure (Category C) account for the biggest number of incidents captured in this study (46.2%). Although the majority of customers within Category B and C evaluated the recovery efforts as satisfactory, majority of others in the other categories assessed otherwise. The dynamics of these findings can help service providers to understand the underlying events or incidents that lead to customer satisfaction and dissatisfaction and eventually to improve their online service strategies.